PENGARUH PENERAPAN METODE JARIMATIKA TERHADAP KEMAMPUAN MENGHITUNG PERKALIAN SISWA KELAS 3 SDN 03 WRINGINPUIH TAHUN AJARAN 2021/2022 - Eka Putri Wulandari; Nur Wiarsih; Meliantina Meliantina (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2022)
This study aims to determine the effect of the Jarimatika method on the ability to calculate multiplication of grade 3 students at SDN 3 Wringinputih Muncar in the 2021/2022 academic year. The background of this research is where in the learning process mathematics teachers still use the lecture method and in multiplication material the teacher only uses memorization techniques, and not all students have a strong memory to master multiplication memorization. So that students have difficulty in working on math problems, especially in multiplication. Jarimatika is one of the counting methods in the operation of Ka Ba Ta Ku (multiply-plus-subtract) using the fingers. The type of research used is quantitative with an experimental method in the form of a one-group pretest-posttest design. The population in this study were all third grade students of SD Negeri 03 Wringinputih Muncar with a total of 29 students. Sampling in this study used a non-probability sampling technique of saturated sampling, so that the sample obtained was class III with a total of 14 students. Data collection techniques in this study used several methods, namely the method of observation, interviews, tests and documentation. The data analysis technique used validity test, reliability test, normality test, homogeneity test and paired sample t-test. The results obtained based on the results of the analysis of the paired samples t-test obtained the value of sig. (2-tailed) of 0.000 with a significant level of = 0.05 which means 0.000 <0.05 then Ha is accepted. Meanwhile, it is known that the data df = 28, significant level = 0.05, tcount = -9.011 and ttable = 2.048 so that it can be stated that the tcount value is greater than ttable means -9.011 > 2,048, then Ho is rejected and Ha is accepted, meaning the use of the Jarimatika method on the ability to calculate multiplication in Mathematics in class III. With the difference between the average value (mean) of the posttest and the average value (mean) of the pretest is 40.00 (posttest = 70.34 and pretest = 30.34), which means the average value of the posttest is higher than the value of the pretest. Thus, it can be concluded that the application of the Jarimatika method has a significant effect on the results of the ability to calculate the multiplication of class III SD Negeri 03 Wringinputih Muncar in the 2021/2022 school year.